Digitalisasi Dalam Mempengaruhi Partisipasi Politik: Studi Kasus pada Petisi Online “Gratiskan Vaksin Covid-19 Untuk Semua Rakyat Indonesia!” - Dwini Rahmadina Nisahati (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
ABSTRACT After the government announced that there will be two corona virus vaccination schemes; government program vaccination and self-vaccination, the public gave a disapproving reaction by raising an online petition on the Change.org website asking the government to make vaccines free for all Indonesians. Within five days, there were more than 7500 virtual signatures supporting the policy from the initial target of 2500 signatures. As a result, the government decided to make vaccines free for all Indonesians. By using literature review research method, this qualitative paper came to conclusion that the online petition entitled